Effect of Extrusion Speed on the Microstructures and Density of Compaction Efficiency in Powder Pressing. Issue 208 (12th June 2020) - Xiao-Yan, Wu; Long-Zhang, Shen; Tai-ping, Peng; Yong, Liu
Abstract: Powder metallurgy is an effective process of manufacturing near net shape products. It offers many advantages, including high productivity, low production costs less energy consumption and environmental friendship, which is widely concern in powder metallurgy industry. In this paper, the effects of pressing parameters, such as pressing pressure, pressing speed and holding time, on the density of blanking Fe-based amorphous alloys at room temperature are studied. The experimental results show that with the increase of pressure, the density of the blank has just started to increase faster, but the pressing pressure cannot exceed the limit of the die. Accelerating the pressing speed is helpful to increase the density of the compact at the very beginning, but with the pressing speed exceeding one value, the density of the blank decreases. The pressure time is not particularly obvious to the density of the blank, and the general holding time is two minutes.